UMPSA and Public Islamic Bank Berhad seal agreement to empower asnaf economy through Program Penternakan Itik Penelur (KELIP - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 13 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Public Islamic Bank Berhad (PIBB) today signed a Memorandum of Agreement (MoA) to implement the Program Penternakan Itik Penelur (KELIP), a strategic initiative aimed at empowering the economic wellbeing of the asnaf (eligible zakat recipients) community through a high-impact and sustainable livestock sector.